2015
DOI: 10.1161/hypertensionaha.115.05472
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Blood Pressure Variability, New-Onset Diabetes Mellitus, and New-Onset Chronic Kidney Disease in the Japanese General Population

Abstract: T he association between higher blood pressure (BP) and chronic kidney disease (CKD) has been well established. [1][2][3] In addition to average BP values, BP variability (BPV) may be associated with CKD.4-9 BPV consists of shortterm BPV (eg, beat-to-beat and within 24 hour) and long-term BPV (eg, day-by-day and visit-to-visit BPV). 10,11 The implications of long-term BPV are less defined, particularly its effects on kidney.Observational studies examining longitudinal associations between long-term BPV and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 31 publications
1
43
0
3
Order By: Relevance
“…11-13, 28, 29 The associations between obesity (defined by BMI) and BP variability, have been inconsistent. 14-16 In our study, participants with higher BMI had higher long-term ARV SBP with a modest increase in mean SBP across BMIs, whereas an increase in mean SBP with less variable long-term ARV SBP was observed with increasing visceral adiposity. Regional fat distribution may therefore be a determinant of individual BP level and variability, independent of BMI, which would partially explain the complex associations of obesity with BP variability.…”
Section: Discussionmentioning
confidence: 45%
“…11-13, 28, 29 The associations between obesity (defined by BMI) and BP variability, have been inconsistent. 14-16 In our study, participants with higher BMI had higher long-term ARV SBP with a modest increase in mean SBP across BMIs, whereas an increase in mean SBP with less variable long-term ARV SBP was observed with increasing visceral adiposity. Regional fat distribution may therefore be a determinant of individual BP level and variability, independent of BMI, which would partially explain the complex associations of obesity with BP variability.…”
Section: Discussionmentioning
confidence: 45%
“…Increased SBPV was also linked to adverse renal outcomes. One SD higher SBPV was associated with 15% (95% CI: 11% to 20%) higher incidence in renal dysfunction defined as new proteinuria on dipstick, eGFR <60 ml/min1.73 m 2 , or rapid eGFR decline (≥3 ml/min/1.73 m 2 per year) in a nationwide Japanese study including 48,587 participants (37). A post hoc analysis of the Irbesartan Diabetic Nephropathy Trial and the Reduction of End Points in Non-Insulin-Dependent Diabetes with the Angiotensin II Antagonist Losartan study that included 2,739 individuals with baseline nephropathy demonstrated that greater baseline VVV in SBP was associated with higher risk of the composite outcome of doubling serum creatinine, ESRD, or death, but not with cardiovascular outcomes (38).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Yano et al (13) showed that higher SBP variability was associated with the development of proteinuria or eGFR,60 ml/min per 1.73 m 2 among 48,587 Japanese adults without CKD or diabetes. However, studies showing a higher risk for advanced renal disease, such as ESRD, have been restricted to persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In some but not all studies, persons with higher BP variability had more rapid CKD progression as measured by declines in eGFR or increases in urinary albumin (9)(10)(11)(12)(13). Some studies of persons with diabetes have shown an association of BP variability with more clinically impactful renal outcomes, including ESRD (10,14), but such an association has not been shown among persons without diabetes.…”
Section: Introductionmentioning
confidence: 99%